CLINICAL FEATURES OF SKIN LESION IN DEEP MYCOSES AGAINST THE BACKGROUND OF HIV/AIDS - A.M. Daschuk; L.O. Kutsevliak (Проблеми екології та медицини)
Introduction. The incidence of HIV/AIDS infection in Ukraine has reached a considerable scale. One of the earliest markers of HIV/AIDS infection is the skin lesion caused by fungi. Deep mycoses develop in the spread of infection from the skin to the underlying tissues, or as a result of hematogenous dissemination. Due to the fact that HIV/AIDS infection has gone beyond the vulnerable groups (commercial sex workers, injecting drug users, etc.), knowledge and alertness of doctors about the unusual clinical manifestations of dermatoses may be a factor in early diagnosis of HIV/AIDS. Timely diagnosis, treatment and conduction of anti-epidemic measures will reduce the incidence of HIV/AIDS infection in Ukraine. Treatment of concomitant HIV-related fungal skin lesions can improve the effectiveness of antiretroviral therapy. The aim of the research was to study the clinical picture, diagnostics and treatment of deep mycoses in HIV/ AIDS infected patients. Methods. The analysis of the scientific literature on the etiology, pathogenesis, clinical picture, diagnosis and treatment of deep mycoses in patients with HIV/AIDS infection has been conducted. Conclusions. The treatment of deep mycoses in HIV/AIDS infection is quite difficult and requires continuous use of antifungal agents.